Post burn contracted neck: Experience in Ain Shams burn center - Amr Mabrouk; Mai Raafat Hammad; Adel Mabrouk; Mohamed Samir Badawy (Elsevier, 2024)
Introduction: The neck is especially liable to severe contractures following burns, especially in developing countries. Severe neck contractures are functionally devastating as they can also result in respiratory compromise and intubation difficulties. In this study, we examine out experience with neck contractures over a period from January 2019 through July 2022 in Ain Shams University burn unit, which receives referrals from all over Egypt, most of which are challenging due to late presentation. Methods: We prospectively evaluated 70 patients with post-burn neck contracture, and surgically managed them according to Makboul and El-Oteify's classification of neck contractures. Interventions for release included use of skin grafts, local flaps, tissue expansion and free tissue transfer. Recurrence was also correlated to method on release. Conclusion: The most common grade of contracture was moderate (n=34). Broad scars comprised the most common pattern of scar (n=32). Recurrence of neck contracture increased with release by skin grafts (28.6%).